Disparitas Dan Kekosongan Hukum Pidana Atas Kecelakaan Konstruksi Dan Kegagalan Bangunan Dalam Jasa Konstruksi - Eddy, Triono; Agustina, Agustina; Purnomo, Sagita (Universitas Widya Gama Malang, 2023)
This study aims to comprehensively discuss legal sanctions for construction accidents and building failures in construction services law, as well as discuss in depth efforts to overcome disparities and criminal law vacancies for building failures in construction services law. This type of research is normative juridical with a descriptive-analytical approach, discusses existing legal symptoms and problems and tests them aware of laws and legal norms. The results of this study show that legal sanctions for construction accidents and building failures in the construction services law are divided into two, namely administrative sanctions (written warnings, administrative fines, temporary suspension of construction service activities, inclusion in the blacklist, suspension of permits and/or revocation of permits) and civil sanctions (compensation), Meanwhile, criminal sanctions are regulated in laws outside construction services such as the Building Law and the Housing/Settlement Law, namely (imprisonment and fines). Efforts to overcome disparities and vacancies in criminal law for construction accidents and building failures are through codification or legal reconstruction, namely: rearranging criminal sanctions for building failure in the construction services law and establishing or combining several provisions of related laws in the field of construction, especially regulating building failures and construct accidents regulated in Law Number : 28 of 2002 concerning Building and Law Number : 1 of 2011 concerning Housing and Settlement Areas.